Viral dedication to vigorous destruction of interferon receptors - Xia, Chuan (Virology, 2018)
Interferons (IFNs) exhibit forceful inhibitory activities against numerous viruses by inducing synthesis of anti-viral proteins or promoting immune cell functions, which help eradicate the vicious microbes. Consequently, the degree to which viruses evade or counterattack IFN responses influences viral pathogenicity. Viruses have developed many strategies to interfere with the synthesis of IFNs or IFN receptor signaling pathway. Furthermore, multiple viruses decrease levels of IFN receptors via diverse tactics, which include decreasing type I IFN receptor mRNA expression, blocking post-translational modification of the receptor, and degrading IFN receptors. Recently, influenza virus was found to induce CK1α-induced phosphorylation and subsequent degradation of the receptor for type I and II IFNs. In this review, viral mechanisms that remove IFN receptors are summarized with an emphasis on the mechanisms for virus-induced degradation of IFN receptors.